Amygdala response predicts clinical symptom reduction in patients with borderline personality disorder: A pilot fMRI study - Geurts, Dirk E. M.; Van den Heuvel, Thom J.; Huys, Quentin J. M.; Verkes, Robbert J.; Cools, Roshan (Frontiers in Behavioral Neuroscience, 2022)
Borderline personality disorder (BPD) is a prevalent, devastating and heterogeneous psychiatric disorder. Treatment success is highly variable within this patient group. A cognitive neuroscientific approach to BPD might contribute to precision psychiatry by identifying neurocognitive factors that predict who will benefit from a specific treatment. Here we build on observations that BPD is accompanied by enhanced impact of aversive affect on behavior and abnormal neural signaling in the amygdala. We assessed whether BPD is accompanied by abnormal aversive regulation of instrumental behavior and associated neural signaling, in a manner that is predictive of symptom reduction after therapy. We tested a clinical sample of 15 female patients with BPD, awaiting dialectical behavior therapy (DBT), and 16 matched healthy controls using fMRI and an aversive Pavlovian-to-instrumental transfer (PIT) task that assesses how instrumental behaviors are influenced by aversive Pavlovian stimuli. Patients were assessed one year after the start of DBT to quantify changes in BPD symptom severity. At baseline, behavioral aversive PIT and associated neural signaling did not differ between groups. However, BOLD signal in the amygdala measured during aversive PIT was associated with symptom reduction at one-year follow-up: Higher PIT-related aversive amygdala signaling before treatment was associated with reduced clinical improvement at follow-up. Thus, within the evaluated group of BPD patients, the BOLD signal in the amygdala before treatment was related to clinical symptom reduction one year after the start of treatment. The results suggest that less PIT-related responsiveness of the amygdala increases chances for treatment success. We note that the relatively small sample size is a limitation of this study and that replication is warranted.